Terapi Kanker Payudara Stadium Lanjut HER2 (+) - Hastarita Lawrenti (Cermin Dunia Kedokteran, 2023)
Approximately 15-20% of breast cancers harbor human epidermal growth factor receptor 2 (HER2) overexpression and/or amplification. This subtype of breast cancer is associated with aggressive behavior, high recurrence rates, and worse prognosis. However, with the introduction of HER2-targeted therapy, trastuzumab, the survival rates have greatly improved. In patients with HER2 positive advanced disease, taxane in combination with trastuzumab and pertuzumab is given in the first-line setting. In the second-line setting and beyond, several emerging anti-HER2 therapies are becoming available including trastuzumab deruxtecan, tucatinib, T-DM1, neratinib, lapatinib, pyrotinib, margetuximab.